(untitled) (Fiep Bulletin - online, 2014)
The purpose of this article is to address the football about two points of view: as a processed product in sporting spectacle and as an important cultural expression of the country. For this reason it mentions events of June 2013, upon completion of the Confederations Cup in Brazil, test event for the World Cup, when protests emerged thousands of Brazilians who were revolted against the abuse of power in relation to the public administration and exorbitant spending of the federal government in the country to host these two sporting events. Regarding to football, it is wondered if the manifestations are against globalized football, against football or against the expression of a national passion, or even if the society shares with the organization of sporting events, in the name of success, adopts a transparent management and targeted the interests of few people, excluding the local population’s access to games. To reflect about it and to understand the significance of these recent events involving the country and manifestation, especially those who are concerned about the Confederations Cup and the World Cup, bibliographical research, taking as reference authors who assume a critical line analysis of these issues. Talking about the discussion of football as a popular event and global football, it evaluates that among the reasons that led the demonstrations against football in the football country, are spending with abusive constructions sports arenas rather than investment in public services essential to life, the understanding that the tournaments are for the elite and not for the population and the possible loss of cultural identity as a result of the globalized world.